Choosing Wisely in Pediatric Hospital Medicine: 5 New Recommendations to Improve Value - Tchou, Michael J; Schondelmeyer, Amanda C; Alvarez, Francisco; Holmes, Alison V; Lee, Vivian; Lossius, Michele N; O'Callaghan, James; Rajbhandari, Prabi; Soung, Paula J; Quinonez, Ricardo (Hospital pediatrics, 2021)
The health care system faces ongoing challenges due to low-value care. Building on the first pediatric hospital medicine contribution to the American Board of Internal Medicine Foundation Choosing Wisely Campaign, a working group was convened to identify additional priorities for improving health care value for hospitalized children. A study team composed of nominees from national pediatric medical professional societies was convened, including pediatric hospitalists with expertise in clinical care, hospital leadership, and research. The study team surveyed national pediatric hospitalist LISTSERVs for suggestions, condensed similar responses, and performed a literature search of articles published in the previous 10 years. Using a modified Delphi process, the team completed a series of structured ratings of feasibility and validity and facilitated group discussion. The sum of final mean validity and feasibility scores was used to identify the 5 highest priority recommendations. Two hundred seven respondents suggested 397 preliminary recommendations, yielding 74 unique recommendations that underwent evidence review and rating. The 5 highest-scoring recommendations had a focus on the following aspects of hospital care: (1) length of intravenous antibiotic therapy before transition to oral antibiotics, (2) length of stay for febrile infants evaluated for serious bacterial infection, (3) phototherapy for neonatal hyperbilirubinemia, (4) antibiotic therapy for community-acquired pneumonia, and (5) initiation of intravenous antibiotics in infants with maternal risk factors for sepsis. We propose that pediatric hospitalists can use this list to prioritize quality improvement and scholarly work focused on improving the value and quality of patient care for hospitalized children.